2018
DOI: 10.1017/hpl.2018.40
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory study of astrophysical collisionless shock at SG-II laser facility

Abstract: Astrophysical collisionless shocks are amazing phenomena in space and astrophysical plasmas, where supersonic flows generate electromagnetic fields through instabilities and particles can be accelerated to high energy cosmic rays. Until now, understanding these micro-processes is still a challenge despite rich astrophysical observation data have been obtained. Laboratory astrophysics, a new route to study the astrophysics, allows us to investigate them at similar extreme physical conditions in laboratory. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This setup has yielded promising results at the Omega Laser Facility [19][20][21] and the National Ignition Facility (NIF), 22,23 as well as at many other laser facilities all over the world. [24][25][26] Recently, experiments on collisionless shocks in plasma flows in which there was a significant self-generated magnetic field showed, for the first time, the formation of magnetized collisionless shocks, with the generation of Weibel instability and observation of electron acceleration in the turbulent structure. 27 Most recently, the dynamics of the ion Weibel instability have been characterized by local quantitative measurements of ion current filamentation and magnetic field amplification in interpenetrating plasmas via optical Thomson scattering (TS).…”
Section: Introductionmentioning
confidence: 99%
“…This setup has yielded promising results at the Omega Laser Facility [19][20][21] and the National Ignition Facility (NIF), 22,23 as well as at many other laser facilities all over the world. [24][25][26] Recently, experiments on collisionless shocks in plasma flows in which there was a significant self-generated magnetic field showed, for the first time, the formation of magnetized collisionless shocks, with the generation of Weibel instability and observation of electron acceleration in the turbulent structure. 27 Most recently, the dynamics of the ion Weibel instability have been characterized by local quantitative measurements of ion current filamentation and magnetic field amplification in interpenetrating plasmas via optical Thomson scattering (TS).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present the new petawatt-based laser wakefield acceleration facility. We also present in detail an online plasma density diagnostic employing the Nomarski interferometry [28][29][30][31][32][33][34] and show its importance toward the generation of LWFA electron beams.…”
Section: Articlementioning
confidence: 99%
“…It is di cult to take a direct observation of astrophysical parameters in extreme celestial events limited by the current technology. The acceleration process of high-energy charged particles based on relativistic laser plasma interactions has been studied, which provides a superhigh acceleration gradient 7 . Kuramitsu et al reported the simulation of a large-size relativistic laser-induced incoherent wake eld in low-density plasma.…”
Section: Introductionmentioning
confidence: 99%